Asuhan Keperawatan Pada Ny. F Keluarga Tn. S Dengan Gangguan Sistem Pernafasan : Tuberkulosis Paru Di Desa Kutayu RT.01 RW.02 Kecamatan Tonjong Kabupaten Brebes - Zaetun Naimah; Esti Nur Janah; Siti Fatimah (Jurnal Medika Nusantara, 2023)
The family has an important role in recognizing health problems that exist in society. As families deal with diseases that many people suffer from due to unhealthy lifestyles and irregular eating patterns, such as stroke, heart disease, diabetes, tuberculosis (TB), hypertension and lung disease (Apriliani et al., 2020). Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis. This disease enters the body through the air in the lungs and spreads to other parts of the body through the blood system, lymphatic system, respiratory tract (bronchi) or directly to other parts of the body (Faturrahman et al., 2021). In 2021 there were TB cases in Southeast Asia (45%), Africa (23%) and the Western Pacific (18%), with smaller cases in the Eastern Mediterranean (8.1%), America (2.9%) and Europe (2.2%). The 30 countries with high TB ??cases account for 87% of the estimated cases worldwide, and 8 of these countries account for more than two-thirds of the global total: India (28%), Indonesia (9.2%), China ( 7.4%), Philippines (7.0%), Pakistan (5.8%), Nigeria (4.4%), Bangladesh (3.6%) and Democratic Republic of Congo (2.9%) (WHO, 2022).